Health Risk Assessment of Volatile Organic Compounds for Children in Indoor Air, Ulaanbaatar, Mongolia - Oyun-Erdene Otgonbyamba; Gantuya Ganbat; Ser-Od Khuyag; Enkhjargal Altangerel; Bilguun Ganbold; Altangadas Bayanjargal; Altangerel Bat-Erdene; Bataa Chuluunbaatar; Burmaajav Badrakh; Suvd Batbaatar (Aerosol and Air Quality Research)
Abstract This study presents levels of volatile organic compounds (VOCs) measured indoors for the first time in Ulaanbaatar, Mongolia, and quantifies the health risk for children emphasizing the urgent need to improve control for indoor VOCs sources. The 583 samples collected at 144 sites, including new buildings, old apartments, schools, workplaces, kindergartens, baishin, and Mongolian traditional gers, hospitals, schools, and shopping centers are analyzed. Formaldehyde was detected in 95.7% of the samples, while benzene was in 24.2%. The levels of benzene, toluene, and xylene in new and old buildings and apartments exceed the recommended values of AGÖF for volatile organic compounds in indoor air. The probabilistic Monte Carlo simulation method was used to estimate the risk exposure of four types of VOCs (benzene, formaldehyde, toluene, and m,p-xylene) to the health of the study population. The risk of cancer for benzene and formaldehyde is high in the age group of 7 months—4 years, m,p-xylene, and toluene show non-cancer risk in this age group.